[Comment] Pelvic floor rehabilitation after rectal cancer surgery: a multicenter randomized clinical trial(FORCE trial)[J].Ann Surg - Chi Zhaocheng (结直肠肛门外科, 2022)
[Objective] To investigate the effects of PFR after LAR compared to usual care without PFR. [Summary of background data] Functional complaints, including fecal incontinence, often occur after LAR for rectal cancer. Controversy exists about the effectiveness of PFR in improving such postoperative functional outcomes. [Methods] This was a multicenter, randomized controlled trial involving 17 Dutch centers. Patients after LAR for rectal cancer were randomly assigned (1:1) to usual care or PFR and stratified by sex and administration of neoadjuvant therapy. Selection was not based on severity of complaints at baseline. Baseline measurements were taken 3 months after surgery without temporary stoma construction or 6 weeks after stoma closure. The primary outcome measure was the change in Wexner incontinence scores 3 months after randomization. Secondary outcomes were fecal incontinence-related quality of life, colorectal-specific quality of life, and the LARS scores. [Results] Between October 2017 and March 2020, 128 patients were enrolled and 106 randomly assigned (PFR n = 51, control n = 55); 95 patients (PFR n = 44, control n = 51) were assessable for final analysis. PFR did not lead to larger changes in Wexner incontinence scores in nonselected patients after LAR compared to usual care [PFR: -2.3, 95% confidence interval (CI) -3.3 to -1.4, control: -1.3, 95% CI -2.2 to -0.4, P = 0.13]. However, PFR was associated with less urgency at follow-up (odds ratio 0.22, 95% CI 0.06-0.86). Patients without near-complete incontinence reported larger Wexner score improvements after PFR (PFR: -2.1, 95% CI -3.1 to -1.1, control: -0.7, 95% CI -1.6 to 0.2, P = 0.045). For patients with at least moderate incontinence PFR resulted in relevant improvements in all fecal incontinence-related quality of life domains, while the control group deteriorated. These improvements were even larger when patients with near-complete incontinence were excluded. No serious adverse PFR-related events occurred. [Conclusion] No benefit was found of PFR in all patients but several subgroups were identified that did benefit from PFR, such as patients with urgency or with at least moderate incontinence and no near-complete incontinence. A selective referral policy (65%-85% of all patients) is suggested to improve postoperative functional outcomes for patients after LAR for rectal cancer.